KENYA’S FOREIGN TRADE BALANCE: AN EMPIRICAL INVESTIGATION - Osoro Kennedy (European Scientific Journal, ESJ, 2013)
This paper investigates the major determinants of trade balance using annual data for the period 1963-2012. It explores the long run and short run determinants of trade deficit using Johansen co integration approach and Error correction modeling (ECM). The results of the investigation indicate that the coefficients of trade balance are positively correlated with budget deficits, FDI and exchange rates. The results show that FDI has a positive effect on trade balance because the trade balance in Kenya is negative. The estimation results also show that the real exchange rate depreciations improve the trade balance in a strong and significant way. This can be attributed to a huge negative trade balance and/or a large positive net foreign direct investment position, which is an indication that the trade balance is much less sensitive to movements in the real effective exchange rate.